Nano Online 2016
DOI: 10.1515/nano.12951_2014.4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an 11-nm DMSA-coated iron nanoparticle on the gene expression profile of two human cell lines, THP-1 and HepG2

Abstract: Background: Iron nanoparticles (FeNPs) have attracted increasing attention over the past two decades owing to their promising application as biomedical agents. However, to ensure safe application, their potential nanotoxicity should be carefully and thoroughly evaluated. Studies on the effects of FeNPs on cells at the transcriptomic level will be helpful for identifying any potential nanotoxicity of FeNPs and providing valuable mechanistic insights into various FeNPs-induced nanotoxicities. Results: This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Many studies have found that high doses of nanoparticles reduce cell viability, generate reactive oxygen species, induce inflammation, differentiation, apoptosis, and damage DNA. 31 However, low doses of nanoparticles may stimulate the cellular responses. 32 Among three main different cell types of freely circulating immune cells (phagocytes, amoebocytes, and vibratile cells), 1 µg/mL of TiO 2 nanoparticles produced an 10% increase in the relative number of phagocytes ( P = 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have found that high doses of nanoparticles reduce cell viability, generate reactive oxygen species, induce inflammation, differentiation, apoptosis, and damage DNA. 31 However, low doses of nanoparticles may stimulate the cellular responses. 32 Among three main different cell types of freely circulating immune cells (phagocytes, amoebocytes, and vibratile cells), 1 µg/mL of TiO 2 nanoparticles produced an 10% increase in the relative number of phagocytes ( P = 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…67 Interestingly, several pathways related to viral infection (virus entry via the endocytic pathway and hepatic fibrosis pathway) were significantly enriched by the DEGs, and have also been reported to be active in neurotoxicity in rats 8 and cells exposed to iron nanoparticles. 20,68 Based on the gene expression pattern observed in the gene interaction and network analysis, it appears that genes responsible for induction of the immune response, cell adhesion and migration, type I interferon signaling pathway, cell proliferation, endoplasmic reticulum stress, and unfolded protein response were significantly induced. These biological and cellular processes are required for cancer development and tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…17 As such, it is pertinent to investigate the mechanisms of QD cytotoxicity. Indeed, to assess the global effect of nanoparticles on target cells, transcriptomic profiling has been undertaken in several studies, as in the case of silver and titanium nanoparticles, 18 genotoxic and non-genotoxic carcinogens, 19 11-nm dimercaptosuccinic acid-coated magnetite nanoparticles, 20 and for fibroblasts. 21 The aim of this study is thus to investigate the effects of CdTe-QD exposure in Chang cancer cells via microarray gene expression profiling to explore their oncogenic potential in terms of causing a more aggressive form of cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DMSA-coated Fe 3 O 4 magnetic nanoparticle (FeNP) were provided by the Biological and Biomedical Nanotechnology Group of the State Key Lab of Bioelectronics, Southeast University, Nanjing, China 56 . This FeNP was characterized by our previous study 36,[57][58][59][60] . A magnetic transfection agent (MagTransf TM ) was purchased from the Nanjing Nanoeast Biotech co., ltd (Nanjing, China), which was referred to as FeNC in this study.…”
Section: Methodsmentioning
confidence: 99%